2016
DOI: 10.1016/j.jamcollsurg.2016.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Successful Completion of the Pilot Phase of a Randomized Controlled Trial Comparing Sentinel Lymph Node Biopsy to No Further Axillary Staging in Patients with Clinical T1-T2 N0 Breast Cancer and Normal Axillary Ultrasound

Abstract: Background Axillary surgery is not considered therapeutic in patients with clinical T1-T2 N0 breast cancer. The importance of axillary staging is eroding in an era where tumor biology, as defined by biomarker and gene expression profile, is increasingly important in medical decision making. We hypothesize that axillary ultrasound (AUS) is a noninvasive alternative to sentinel lymph node biopsy (SLNB), and AUS could replace SLNB without compromising patient care. Study Design Patients with clinical T1-T2 N0 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
0
15
1
2
Order By: Relevance
“…Some clinical trials such as the BOOG 2013-08 ( 14 ), NCT 01821768 ( 15 ), and the SOUND ( 16 ) have been conducted recently, and breast cancer patients with negative US/FNAB findings were randomly assigned to SLNB and non-SLNB groups. These clinical trials demonstrated that it was necessary to perform SLNB in patients with negative US-guided FNAB of suspicious lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical trials such as the BOOG 2013-08 ( 14 ), NCT 01821768 ( 15 ), and the SOUND ( 16 ) have been conducted recently, and breast cancer patients with negative US/FNAB findings were randomly assigned to SLNB and non-SLNB groups. These clinical trials demonstrated that it was necessary to perform SLNB in patients with negative US-guided FNAB of suspicious lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Van Wely et al [20] also confirmed the same in their meta-analysis. Deurloo et al [8], Baruah et al [12], and Cyr et al [21] also noted that micrometastasis and isolated tumor cellpositive patients had poor identification rates in preoperative US. Pilewskie et al [22] also noted that finding an abnormal node on preoperative axillary imaging was significantly associated with having more than three total positive nodes on final pathology (p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…Careful selection of a cohort of patients who may benefit from axillary ultrasound imaging alone and be exempt from SNB may yet be possible. Cyr and co‐workers undertook a pilot‐phase RCT comparing SNB with no further axillary staging in patients with cT1–T2 N0 breast cancer and normal axillary ultrasound findings. In 68 patients, with 34 randomized to each arm and median follow‐up of 17 (range 1–32) months, no recurrences were recorded, but there were two instances of lymphoedema, one wound infection, two seromas, one haematoma and one case of paraesthesia in the SNB arm.…”
mentioning
confidence: 99%